2008
DOI: 10.1002/ajmg.a.32279
|View full text |Cite
|
Sign up to set email alerts
|

Live birth prevalence of Down syndrome in Tottori, Japan, 1980–1999

Abstract: One hundred sixty-four patients with Down syndrome (DS) were confirmed in Tottori Prefecture, Japan, from 1980 to 1999. The sex ratio of 1.52 (99 males and 65 females) was comparable to that reported in previous studies. The live birth prevalence per 1,000 was 1.52 (95% CI: 1.29-1.75) from 1980 to 1999, with a prevalence of 1.34 (95% CI: 1.05-1.63) recorded between 1980 and 1989, and 1.74 (95% CI: 1.37-2.11) between 1990 and 1999. There was no statistically significant change between these two decades (chi(2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Gender distribution is fairly balanced in our registries (51.3% male), compared to 53.1% males among the Down's cases of Balkan et al (2010) and 54.6% males by Duarte et al (2004); however, Takeuchi et al (2008) reported a gender ratio of 1.55.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Gender distribution is fairly balanced in our registries (51.3% male), compared to 53.1% males among the Down's cases of Balkan et al (2010) and 54.6% males by Duarte et al (2004); however, Takeuchi et al (2008) reported a gender ratio of 1.55.…”
Section: Discussioncontrasting
confidence: 47%
“…It was reported that DS prevalence was increased from 9.0 to 11.8 per 10,000 live births in 10 USA regions during a 25-year period (Olsen et al, 2003;Shin et al, 2009 The live birth prevalence of DS has been increasing in Japan since 1970; the increasing frequency of DS is attributed to advanced maternal age (Hoshi et al, 1999;Kajii, 2008;Takeuchi et al, 2008). In contrast, the live birth prevalence of DS has decreased (from 1.17 to 0.89/1000) over the years, from 1993 to 1998 in Singapore, due to antenatal diagnosis and elective abortion (Lai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, Down syndrome is less common in the Japanese and black populations. [9][10][11] The fewer number of cases of concurrent moyamoya disease and Down syndrome in these ethnicities may be secondary to a lower proportion of patients with Down syndrome in these populations. The contribution of Down syndrome to moyamoya disease in patients $ 15 years of age decreases, and other factors such as hypertension and diabetes mellitus assume greater importance.…”
Section: Discussionmentioning
confidence: 99%
“…Reported live birth rates vary greatly between countries from 0.23 per 1,000 in Taiwan (Jou et al., 2005), to 2.98 in Ireland (O'Nuallain, Flanagan, Raffat, Avalos, & Dineen, 2007), reflecting differences in maternal age, access to antenatal diagnosis, and social attitudes toward termination of pregnancy. While live birth rates with Down syndrome have declined in Taiwan (Jou et al., 2005), Singapore (Lai et al., 2002), and France (Khoshnood, De Vigan, Vodovar, Goujard, & Goffinet, 2004), live birth rates are increasing in Ireland (O'Nuallain et al., 2007), Japan (Takeuchi et al., 2008), and Hungary (Metneki & Czeizel, 2005). The overall prevalence of people with Down syndrome is expected to increase for some time due to dramatic increases in median and average life expectancy, even where there is a drop in live birth rates.…”
Section: Demographicsmentioning
confidence: 99%